Frankliniella species from India (Thysanoptera: Thripidae), with a new generic synonym and an unusual new species - Pal, Shash; Patidar, Abhishek; Kumar, Vikas; Panjaliya, Rakesh Kumar; Tyagi, Kaomud (Zootaxa, 2023)
Frankliniella genus-group is one of the most important group in the sub-family Thripinae comprising, more than 270 species in nine genera. A morphological-based cladistic analysis of genus-level relationships within this group was performed, based on 54 morphological character states for 26 species, including Thrips physapus as an outgroup. This analysis recovered Pseudanaphothrips as monophyletic and sister-group to a group of five Old World genera: Firmothrips, Kakothrips, Parabaliothrips, Sitothrips and Yaobinthrips. It also showed a sister relationship between eight species of Poaceae-associated Old World species in Frankliniella plus Iridothrips, and a group of five New World species in Frankliniella and Guerothrips. As a result, Iridothrips is here considered a new synonym of Frankliniella, and Frankliniella insolitum sp. n. is described from northern India. A key to the six species of Frankliniella recorded from India is also provided. Images and notes of F. unicolor Morgan based on a paratype of the synonym F. andropogoni Moulton & Andre are also provided.